Physico-Chemical Processes - Hua, Bin (Water environment research : a research publication of the Water Environment Federation, 2016)
This review is on the research literature published in 2015 related to the physico-chemical processes for water and wastewater treatment. The review is divided into six sections, including filtration, sedimentation, coagulation/flocculation, flotation, oxidation, and adsorption